Identification and Expression Analysis of Wheat Golden2-like (TaGLK) Gene in Response to Biotic and Abiotic Stress - Junhui Xiang; Pingu Liu; Daniel Bimpong; Jiayi Shen; Xusi Liu; Siting Wang; Yan Li; Youning Wang; Dongfang Ma (Agronomy)
The Golden2-like (GLK) transcription factors belong to the GARP family of transcription factors and play significant roles in plant growth, development, and responses to both abiotic and biotic stresses. This study employed bioinformatics and expression analyses to investigate the regulatory roles of wheat GLK proteins under various stress conditions, including abscisic acid (ABA) treatment, osmotic stress, and infection by Fusarium graminearum. The study identified 125 TaGLK proteins and revealed that TaGLKs play a significant role in wheat’s development and response to adverse environmental conditions. The results indicate that TaGLKs may serve as potential transcriptional regulators capable of integrating multiple cellular signals to coordinate various developmental and physiological processes. Evolutionary analysis classified the TaGLK proteins into six subgroups, which shared similar conserved domains and motifs. Protein–protein interaction network analysis revealed that TaGLKs are involved in photoreceptor activity, cell cycle progression, and protein regulation. Gene expression analysis of TaGLKs discovered that they play key functions in wheat development, as well as regulation of biotic and abiotic stress conditions. RT-qPCR analysis showed that TaGLKs regulate earlier and late effects of osmotic stress, F. graminearum infections, and ABA treatment in wheat. These findings provide knowledge for future studies of the functions of TaGLK TFs in wheat stress tolerance and development, which could have significant implications for enhancing wheat tolerance to various environmental stressors.